Piezoelectric element, its manufacturing method, and piezoelectric vibration device
By using Li, Na, K perovskite-type sodium ion niobate piezoelectric ceramics and hydrolyzing treatment at high temperature to remove Li3NbO4, the adhesion failure and short circuit of lead-based piezoelectric ceramics in high temperature and high humidity environments is solved, and higher durability and electrical insulation are achieved.
Patent Information
- Application Number
- JP2020184243
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-04
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2040-11-04
AI Technical Summary
Existing lead-based piezoelectric ceramics are prone to problems such as adhesion failure, electrode peeling and short circuit in high temperature and high humidity environments, resulting in equipment failure and it is difficult to replace lead-based piezoelectric ceramics with unstable performance in this environment.
Li, Na, K perovskite sodium ion niobate piezoelectric ceramics with Li0.02
In high temperature and high humidity environments, the durability and electrical insulation of piezoelectric components are significantly improved, fault occurrence and short circuit and electrical breakdown risks are reduced.
Smart Images

Figure 0007628013000002 
Figure 0007628013000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a piezoelectric element, a manufacturing method thereof, and a piezoelectric vibration device. [Background technology]
[0002] A piezoelectric element is composed of a piezoelectric body having piezoelectricity and at least a pair of electrodes connected to the piezoelectric body. A piezoelectric element has the property of generating an electric charge by mechanical displacement, and of generating mechanical displacement by a potential difference between the electrodes. Taking advantage of these properties, piezoelectric elements are widely used in sensors, actuators, etc.
[0003] Piezoelectric ceramics, which are sintered bodies having piezoelectricity, are often used as the piezoelectric body that constitutes the piezoelectric element. Lead zirconate titanate (Pb(Zr,Ti)O3, PZT) and its solid solution are widely used as the composition of this piezoelectric ceramic. PZT-based piezoelectric ceramics have the advantage of being usable in high-temperature environments because of their high Curie temperature. In addition, they have the advantage of being able to convert electrical energy and mechanical energy efficiently because they have a high electromechanical coupling coefficient. Furthermore, by selecting an appropriate composition, they can be fired at temperatures below 1000°C, which has the advantage of reducing the manufacturing cost of piezoelectric elements. In this regard, particularly in multilayer piezoelectric ceramics, the use of low-melting-point materials with reduced content of expensive materials such as platinum and palladium for the internal electrodes that are fired simultaneously with the piezoelectric ceramics produces a significant cost reduction effect. However, PZT-based piezoelectric ceramics are problematic because they contain lead, a harmful substance, and lead-free piezoelectric ceramics are being sought to replace them.
[0004] To date, the compositions of lead-free piezoelectric ceramics include alkali niobate ((Li,Na,K)NbO3), bismuth sodium titanate ((Bi 0.5 Na 0.5Various types have been reported, such as niobate (TiO3, BNT) based, bismuth layer compound based, and tungsten bronze based. Of these, alkali niobate based piezoelectric ceramics have a high Curie point and a relatively large electromechanical coupling coefficient, and are therefore attracting attention as an alternative to PZT based piezoelectric ceramics.
[0005] For example, Patent Document 1 reports that a piezoelectric element having first and second electrodes with a silver content of 50% by weight or more, and a piezoelectric ceramic layer disposed between the first and second electrodes and composed of a polycrystalline alkali niobate-based piezoelectric ceramic containing silver and at least one alkaline earth metal selected from calcium, strontium, and barium, can achieve high electrical resistance and piezoelectricity. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2017-163055 A Summary of the Invention [Problem to be solved by the invention]
[0007] In order to put such piezoelectric elements using alkali niobate piezoelectric ceramics into practical use, emphasis is being placed on improving durability in addition to improving mechanical displacement performance and increasing the amount of generated charge. For example, it is considered preferable to be able to suppress the occurrence of failures such as the piezoelectric element falling off the substrate, the members bonded to the piezoelectric element falling off, and the electrodes peeling off from the surface of the piezoelectric element when the piezoelectric element and various devices equipped with the piezoelectric element are placed in a high-temperature and high-humidity environment that is not expected under normal usage conditions due to user carelessness or unavoidable circumstances.
[0008] SUMMARY OF THE PRESENT EMBODIMENTS The present invention has an object to provide a piezoelectric element using an alkali niobate piezoelectric ceramic, which is less likely to break down even when placed in a high-temperature and high-humidity environment.
Means for Solving the Problem
[0009] In order to solve the above problems, the present inventor conducted various studies. As a result, it was hypothesized that the failure that occurs when a piezoelectric element is placed in a high-temperature and high-humidity environment is caused by Li3NbO4 present on the surface of an alkali niobate-based piezoelectric ceramic or at the interface with an electrode disposed thereon. Then, further studies were conducted on a method for removing this Li3NbO4. As a result, it was found that by placing the sintered body obtained by firing in water at a temperature higher than room temperature before forming an electrode on the surface, this can be removed simply and efficiently, and the adhesive strength with the substrate and the electrode is maintained even in a high-temperature and high-humidity environment, leading to the completion of the present invention.
[0010] That is, the first aspect of the present invention for solving the above problems is a piezoelectric element formed of a piezoelectric ceramic containing, as a main component, a perovskite-type compound represented by the composition formula Li x Na y K 1-x-y NbO3 (where 0.02 < x ≦ 0.1, 0.02 < x + y ≦ 1), containing at least one alkaline earth metal selected from calcium, strontium, and barium and silver, having a sintered body containing LiNbO3 on the surface and not containing LiNbO3 in a portion with a depth of 5 μm or more from the surface, and at least one pair of electrodes formed on the surface of the sintered body.
[0011] Further, the second aspect of the present invention is to prepare a sintered body formed of a ceramic containing, as a main component, a perovskite-type compound represented by the composition formula Li x Na y K 1-x-y NbO3 (where 0.02 < x ≦ 0.1, 0.02 < x + y ≦ 1), containing at least one alkaline earth metal selected from calcium, strontium, and barium and silver, placing the sintered body in water at a temperature higher than room temperature, forming at least one pair of electrodes on the surface of the sintered body after the placement, and performing a polarization treatment by applying a voltage between the at least one pair of electrodes, which is a method for manufacturing a piezoelectric element.
[0012] Furthermore, a third aspect of the present invention is a piezoelectric vibration device including the above-mentioned piezoelectric element and a vibration plate joined thereto. Effect of the Invention
[0013] According to the present invention, it is possible to provide a piezoelectric element using an alkali niobate piezoelectric ceramic, which is unlikely to break down even when placed in a high-temperature and high-humidity environment. [Brief description of the drawings]
[0014] [Figure 1] 1 is a diagram showing X-ray diffraction profiles of the sintered body surface of the piezoelectric elements according to the examples and the comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The configuration and effects of the present invention will be described below with reference to the drawings, together with the technical concept. However, the mechanism of action includes assumptions, and the correctness of such assumptions does not limit the present invention. Furthermore, among the components in the following embodiments, those components that are not described in the claims showing the highest concept are described as optional components. Furthermore, the description of a numerical range (two numerical values connected with "~") includes the numerical values described as the lower and upper limits.
[0016] In this specification, "ceramics" refers to the parts other than the electrodes in a "sintered body" which is a bond between multiple particles. Therefore, a "sintered body" that does not contain electrodes is conceptually described as synonymous with "ceramics." In addition, "piezoelectric ceramics" refers to the above-mentioned "ceramics" that have been subjected to a polarization process to develop piezoelectricity.
[0017] [Piezoelectric element] The piezoelectric element according to the first aspect of the present invention (hereinafter sometimes simply referred to as "the first aspect") is composed of a sintered body formed of an alkali niobate-based piezoelectric ceramic and at least one pair of electrodes formed on its surface.
[0018] The piezoelectric ceramic forming the sintered body has a composition formula Li x Na y K 1-x-y NbO3 (where 0.02 < x ≦ 0.1, 0.02 < x + y ≦ 1) and is mainly composed of a perovskite-type compound represented by this formula. Here, "main component" means the component most contained in terms of mass basis. In the above composition formula, by setting the value of x, that is, the content ratio of Li, to exceed 0.02, the piezoelectric ceramic becomes dense. From this point, the value of x is preferably 0.04 or more, and more preferably 0.06 or more. On the other hand, by setting the value of x to 0.1 or less, excessive generation of conductive compounds such as Li3NbO4 is suppressed, and a piezoelectric ceramic excellent in insulation and durability is obtained. From this point, the value of x is preferably 0.09 or less, and more preferably 0.08 or less. Also, by setting the value of x + y in the above composition formula, that is, the total of the content ratio of Li and the content ratio of Na which is an optional component, to exceed 0.02 and be 1 or less, a piezoelectric ceramic having excellent piezoelectric characteristics is obtained.
[0019] Here, that the piezoelectric ceramic is mainly composed of the perovskite-type compound represented by the above composition formula is confirmed by the following method. First, the diffraction line profile of the piezoelectric ceramic exposed on the surface of the piezoelectric element is measured using an X-ray diffractometer (Rigaku Corporation, RINT2500 series) using Cu-Kα radiation. Next, in the obtained X-ray diffraction profile, a profile derived from the perovskite structure is recognized as the main component, and the ratio of the strongest diffraction line intensity in the diffraction line profile thought to be derived from other crystal structures to the strongest diffraction line intensity derived from the perovskite structure is 10% or less, and the piezoelectric ceramic is judged to be mainly composed of a perovskite compound. Note that, if an electrode is formed on the surface of the piezoelectric ceramic or the piezoelectric ceramic is coated, and the piezoelectric ceramic is not exposed on the surface of the piezoelectric element, the electrode or coating is removed by polishing or the like prior to measurement. Next, carbon is evaporated onto the piezoelectric ceramics determined to be mainly composed of perovskite compounds to impart electrical conductivity, and energy dispersive X-ray spectra (EDS) are measured using a silicon drift type energy dispersive X-ray detector (Appolo, manufactured by Ametech Co., Ltd.) installed on a field emission scanning electron microscope (FE-SEM: S-4300, manufactured by Hitachi High-Technologies Corporation). The voltage during measurement is 10 kV, and KK, Na-K, and Nb-L spectra are used for quantitative evaluation. The measurement is performed over a sufficient period of time so that the line intensity of the KK spectrum is 5000 counts or more. Each spectrum is subjected to atomic number correction, absorption correction, and fluorescence correction (ZAF correction) to calculate the content of each element. Finally, the composition formula is determined by setting the Na and K content ratios relative to the calculated Nb content (mol % or atomic %) as the values of y and 1-xy in the above-mentioned composition formula, respectively, and the piezoelectric ceramics whose main component is a perovskite-type compound represented by the above-mentioned composition formula are those whose determined composition formula is within the range of the above-mentioned composition formula.
[0020] In addition to the main component, the piezoelectric ceramic contains at least one alkaline earth metal selected from calcium, strontium, and barium. By including at least one alkaline earth metal, the piezoelectric ceramic, which is mainly composed of the compound of the composition formula described above, has excellent piezoelectric properties, and also has excellent insulation resistance due to the formation of fine polycrystals. From this point of view, the content of the alkaline earth metal is preferably 0.2 mol or more in total, more preferably 0.4 mol or more, and even more preferably 0.5 mol or more, relative to 100 mol of the main component described above. The upper limit of the content of the alkaline earth metal is not particularly limited, but from the viewpoint of maintaining high piezoelectric performance, it is preferably 5.0 mol or less in total, more preferably 4.0 mol or less, and even more preferably 3.0 mol or less, relative to 100 mol of the main component described above.
[0021] The piezoelectric ceramic contains silver in addition to the main component and alkaline earth metal described above. This makes the sintered particles fine, and the excellent piezoelectric properties are exhibited while the insulation resistance is improved. This is due to the interaction between the alkaline earth metal and silver described above. From the viewpoint of fully exhibiting this effect, the content of silver is preferably 0.5 mol or more, more preferably 0.7 mol or more, and even more preferably 1.0 mol or more, per 100 mol of the main component described above. On the other hand, from the viewpoint of obtaining a piezoelectric element with excellent durability, the content of silver is preferably 5.0 mol or less, more preferably 4.0 mol or less, and even more preferably 3.0 mol or less, per 100 mol of the main component described above.
[0022] The piezoelectric ceramic may further contain 0.1 to 3.0 moles of Li and 0.1 to 3.0 moles of Si per 100 moles of the main component. By containing both elements Li and Si, the piezoelectric ceramic can be densified. In addition, the excess Li and Si that cannot be dissolved in the perovskite structure react to generate highly electrically insulating compounds such as Li2SiO3 and Li4SiO4, which suppresses the generation of conductive compounds such as Li3NbO4, and contributes to suppressing the decrease in the electrical resistivity of the piezoelectric ceramic. In order to enhance this effect, the molar ratio of Si to Li (Si / Li) is preferably 1.0 or more, and more preferably 2.0 or more.
[0023] In order to fully exert the above-mentioned effects, the Li content is more preferably 0.3 mol or more, and even more preferably 0.5 mol or more, relative to 100 mol of the main component. On the other hand, by making the Li content 3.0 mol or less relative to 100 mol of the main component, the generation of conductive compounds such as Li3NbO4 is suppressed, resulting in a piezoelectric ceramic with excellent electrical insulation and durability. From this point of view, the Li content is more preferably 2.0 mol or less, and even more preferably 1.5 mol or less, relative to 100 mol of the main component. Although Li is also a constituent element of the above-mentioned main component, the amount of Li described here does not include Li in the main component. The amount of Li not constituting the main component contained in the piezoelectric ceramic is calculated by measuring the total amount of Li contained in the piezoelectric ceramic using an apparatus capable of quantifying Li, such as a laser irradiation type inductively coupled plasma mass spectrometry (LA-ICP-MASS), and subtracting from the total amount the amount of Li that can be dissolved in the alkali niobate calculated in the method for determining the composition formula of the alkali niobate described above.
[0024] In order to fully exert the above-mentioned effects, the content of Si in the piezoelectric ceramic is more preferably 0.5 mol or more, and even more preferably 1.0 mol or more, relative to 100 mol of the main component. On the other hand, by making the content of Si 3.0 mol or less relative to 100 mol of the main component, the amount of heterophase that does not have piezoelectricity is suppressed, resulting in a piezoelectric ceramic with excellent piezoelectric properties. From this point of view, the content of Si is more preferably 2.5 mol or less, and even more preferably 2.0 mol or less, relative to 100 mol of the main component.
[0025] Furthermore, the piezoelectric ceramic may contain 0 to 2.0 moles of Mn per 100 moles of the above-mentioned main component. When the piezoelectric ceramic contains Mn, its electrical resistance is improved. In order to fully exert this effect, the Mn content is preferably 0.2 moles or more. On the other hand, by setting the Mn content to 2.0 moles or less, high piezoelectric performance can be maintained. The Mn content is preferably 1.5 moles or less, and more preferably 1.0 moles or less.
[0026] Here, the content of each of the elements other than Li relative to the main component is determined by measuring the content of Nb and each of the elements in the piezoelectric ceramics using a high-frequency inductively coupled plasma atomic emission spectrometer (ICP-AES, Thermo Fisher Scientific K.K., iCAP6500), an ion chromatography device (Thermo Scientific, ICS-1600), or an X-ray fluorescence analyzer (XRF, Rigaku Corporation, ZSX Primus-IV), and calculating the number of moles of each of the elements when the content of Nb is 100 moles based on the content ratio of each of the elements relative to Nb.
[0027] As long as the piezoelectric ceramics are mainly composed of the perovskite type compound represented by the above-mentioned composition formula, they may contain other additive elements or compounds within the range in which the desired characteristics are obtained. Examples of additive elements that may be contained include the commonly used Ta and Sb, as well as Sc, Ti, V, Cr, Fe, Co, Ni, Cu, Zn, Y, Mo, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Hf, W, etc.
[0028] The sintered body on the first side may have a layered structure of the piezoelectric ceramic and the electrodes described above. In this case, the first side becomes a so-called multi-layer piezoelectric element, and the electrodes forming the sintered body become internal electrodes.
[0029] When the sintered body includes an internal electrode, the electrode material constituting the internal electrode is not particularly limited as long as it is a material that has high conductivity and is physically and chemically stable in the environment in which the multilayer piezoelectric element is used. Examples of electrode materials that can be used include silver (Ag), copper (Cu), gold (Au), platinum (Pt), palladium (Pd), nickel (Ni), and alloys thereof. Among them, those containing 50% or more by mass of silver are preferred in terms of showing high conductivity. In this case, the content of silver in the electrode material is more preferably 70% by mass or more, and even more preferably 80% by mass or more.
[0030] In the first aspect, the sintered body contains LiNbO3 on its surface. This LiNbO3 is derived from Li3NbO4 contained on the surface of the piezoelectric ceramic immediately after firing. Since Li3NbO4 has a relatively low stability as a compound, it decomposes under the action of moisture in a high-temperature, high-humidity environment. For this reason, when a piezoelectric element having electrodes formed thereon is placed in a high-temperature, high-humidity environment, the adhesive strength between the sintered body and the electrodes may decrease, and the electrodes may peel off. In addition, when a device in which a piezoelectric element having such a sintered body is bonded to other members such as a substrate or a diaphragm via an adhesive is placed in a high-temperature, high-humidity environment, the adhesive strength between the sintered body and the adhesive may decrease, and the piezoelectric element or other members may fall off. Such peeling or falling off causes a breakdown of the device. However, the occurrence of such breakdowns can be suppressed by decomposing or removing Li3NbO4 on the surface of the sintered body and then generating highly stable LiNbO3 by the process described below.
[0031] In addition, generating LiNbO3 after decomposing or removing Li3NbO4 contained in the surface of the sintered body is also preferable in terms of improving the insulation of the piezoelectric element. In other words, if highly conductive Li3NbO4 is present on the surface of the sintered body, current will flow from the electrode in contact with it to the Li3NbO4, causing surface conduction and increasing the risk of short circuit and insulation breakdown. In contrast, generating highly insulating LiNbO3 can reduce these risks.
[0032] Whether the sintered body contains LiNbO3 on its surface can be confirmed by the following method. First, the diffraction line profile of the piezoelectric ceramic part of the sintered body exposed on the surface of the piezoelectric element is measured using an X-ray diffractometer (Ultima IV, manufactured by Rigaku Corporation) using Cu-Kα radiation. The X-ray generation conditions are an acceleration voltage of 40 kV and a current of 40 mA. The measurement is performed by continuously scanning the range of 2θ=10 to 90° in 2θ / θ mode with a sampling width of 0.0200°, a scan speed of 5.0° / min., a divergence slit width of 1°, a divergence vertical limiting slit width of 10 mm, the scattering slit and the receiving slit open, and no monochromatic receiving slit. Note that, if an electrode is formed on the surface of the piezoelectric ceramic or the piezoelectric ceramic is coated, and the piezoelectric ceramic is not exposed on the surface of the piezoelectric element, the electrode or coating is removed by polishing or the like prior to the measurement. Next, the maximum value I of the diffraction intensity in the entire range (2θ = 10 to 90°) of the obtained diffraction line profile is calculated. max and the minimum value I min , and the maximum diffraction intensity in the range of 2θ = 23.4 to 24.0° I 1max and the minimum value I 1min From the above, the normalized diffraction intensity I of LiNbO3 is calculated using the following formula 1. LN Then, the obtained I LN When the value of is 1.2 or more, it is judged that the surface of the sintered body contains LiNbO3.
[0033]
number
[0034] The sintered body contains LiNbO3 on its surface, but does not contain LiNbO3 in the portion 5 μm or deeper from the surface. This is because the formation of LiNbO3 derived from Li3NbO4 described above occurs only near the surface of the sintered body. The sintered body in the first aspect is distinguished from piezoelectric ceramics that contain LiNbO3 uniformly in the sense that LiNbO3 is not contained in the portion away from the surface.
[0035] The absence of LiNbO3 in the portion of the sintered body that is 5 μm or more deep from the surface is confirmed by the following method. First, the entire surface of the sintered body constituting the piezoelectric element is polished to remove 5 μm of the surface. In places where electrodes or coatings are formed on the surface of the sintered body, these are removed to expose the sintered body, and then 5 μm of the surface is removed. Next, the polished sintered body is pulverized to prepare a sample for X-ray diffraction measurement. Next, the diffraction line profile of the X-ray diffraction measurement sample is measured under the same conditions as in the above-mentioned method for confirming the inclusion of LiNbO3 on the surface of the sintered body. Finally, from the obtained diffraction line profile, I was calculated using the above-mentioned formula 1. LN If the calculated value is less than 1.2, it is determined that the portion of the sintered body that is 5 μm or more deep from the surface does not contain LiNbO3.
[0036] In the first aspect, at least one pair of electrodes is formed on the surface of the sintered body. The material, shape and arrangement of the electrodes are not particularly limited as long as they can apply a desired voltage to the piezoelectric ceramic or extract a desired voltage or charge from the piezoelectric ceramic. Examples of the material of the electrodes include silver (Ag), copper (Cu), gold (Au), platinum (Pt), palladium (Pd) and nickel (Ni), as well as alloys thereof. Examples of the shape and arrangement of the electrodes include those that cover almost the entirety of a specific surface of the sintered body, and those that cover exposed parts of the internal electrodes and connect them to every other layer when the sintered body has a layered structure of the piezoelectric ceramic and the internal electrodes.
[0037] On the first side, when the electrode disposed on the surface of the sintered body contains silver, resistance heating during use is suppressed due to its low electrical resistance, and migration of silver when placed in a high-temperature and high-humidity environment is suppressed, which is preferable. In a sintered body containing Li3NbO4 on the surface, components derived from Li3NbO4 decomposed in a high-temperature and high-humidity environment form a silver migration path on the surface of the sintered body and penetrate between the sintered particles of the piezoelectric ceramics to also form a silver migration path between the particles, so there is a risk that silver migration is promoted. On the other hand, in the sintered body on the first side where the surface Li3NbO4 is decomposed or removed and LiNbO3 is generated, since the above-mentioned migration path is not formed, silver migration is suppressed.
[0038] [Method for manufacturing piezoelectric element] The method for manufacturing a piezoelectric element according to the second aspect of the present invention (hereinafter, may be simply described as "second side") prepares a sintered body formed of ceramics containing a perovskite-type compound represented by the composition formula Li x Na y K 1-x-y NbO3 (where 0.02 < x ≦ 0.1, 0.02 < x + y ≦ 1) as a main component and containing at least one alkaline earth metal selected from calcium, strontium, and barium and silver, disposing the sintered body in water at a temperature higher than room temperature, forming at least one pair of electrodes on the surface of the sintered body after the disposition, and performing polarization treatment by applying a voltage between the at least one pair of electrodes.
[0039] The method for obtaining the sintered body is not particularly limited, but it is preferable in terms of cost to adopt a method of mixing powdery raw materials, heat-treating them so that a perovskite-type compound is generated, and then molding and firing them. Hereinafter, an example of the manufacturing method will be described.
[0040] First, powders of a predetermined amount of lithium compound, sodium compound, potassium compound, and niobium compound are mixed and calcined to obtain a composition formula Li x Na y K 1-x-yA calcined powder mainly composed of a perovskite-type compound represented by NbO3 (where 0.02 < x ≤ 0.1, 0.02 < x + y ≤ 1) is obtained.
[0041] The lithium compound, sodium compound, potassium compound, and niobium compound used as raw materials react with each other by calcination to form the composition formula Li x Na y K 1-x-y As long as it is a powder that generates a perovskite-type compound represented by NbO3 (where 0.02 < x ≤ 0.1, 0.02 < x + y ≤ 1), the composition, purity, particle size, etc. are not limited. It may be a compound containing two or more of the elements Li, Na, K, and Nb, or a compound containing other elements that act as additive elements. Examples of lithium compounds that can be used include lithium carbonate (Li2CO3). Examples of sodium compounds that can be used include sodium carbonate (Na2CO3) and sodium bicarbonate (NaHCO3). Examples of potassium compounds that can be used include potassium carbonate (K2CO3) and potassium bicarbonate (KHCO3). Examples of niobium compounds that can be used include niobium pentoxide (Nb2O5).
[0042] The method for mixing the raw material powders is not particularly limited as long as each powder is uniformly mixed while preventing the incorporation of impurities, and either dry mixing or wet mixing may be employed. When wet mixing using a ball mill is employed as the mixing method, for example, it may be mixed for about 8 to 24 hours.
[0043] The calcination conditions are not limited as long as each raw material reacts to obtain a calcined powder mainly composed of a perovskite-type compound represented by the above composition formula. For example, in an air atmosphere, it may be calcined at 700 to 1000 °C for 2 to 8 hours. If the calcination temperature is too low or the calcination time is too short, there is a risk that unreacted raw materials or intermediate products will remain. Conversely, if the calcination temperature is too high or the calcination time is too long, there is a risk that a compound of the desired composition cannot be obtained due to the volatilization of the alkali component, or that the productivity will decrease because the product becomes consolidated and difficult to crush.
[0044] Next, a compound containing at least one alkaline earth metal element selected from the group consisting of Ca, Sr, and Ba, and silver or a compound containing silver are mixed with the calcined powder obtained by calcination to obtain a molding powder. At this time, compounds containing various additive elements such as Li, Si, and Mn may be mixed at the same time.
[0045] The compound containing an alkaline earth metal to be mixed into the calcined powder, and the compound containing silver or a compound containing silver, as well as the compound containing various additive elements to be mixed into the calcined powder as necessary, are not limited in composition, purity, particle size, etc., as long as they can form a ceramic of the desired composition in the finally obtained sintered body. The composition may contain two or more of the additive elements. Examples of usable compounds containing an alkaline earth metal element include calcium compounds such as calcium carbonate (CaCO3), calcium metasilicate (CaSiO3), and calcium orthosilicate (Ca2SiO4), strontium compounds such as strontium carbonate (SrCO3), and barium compounds such as barium carbonate (BaCO3). Examples of usable compounds containing silver include silver oxide (Ag2O). Examples of usable lithium compounds include lithium carbonate (Li2CO3), lithium metasilicate (Li2SiO3), and lithium orthosilicate (Li4SiO4). Examples of usable silicon compounds include silicon dioxide (SiO2), lithium metasilicate (Li2SiO3), lithium orthosilicate (Li4SiO4), calcium metasilicate (CaSiO3), and calcium orthosilicate (Ca2SiO4). Examples of usable manganese compounds include manganese carbonate (MnCO3), manganese monoxide (MnO), manganese dioxide (MnO2), manganese tetraoxide (Mn3O4), and manganese acetate (Mn(OCOCH3)2).
[0046] The method of mixing these compounds with the calcined powder is not particularly limited as long as each powder is mixed uniformly while preventing the inclusion of impurities, and either dry mixing or wet mixing may be used. The mixing may also serve as crushing the calcined powder. When wet mixing using a ball mill is used as the mixing method, mixing may be performed for about 8 to 24 hours, for example.
[0047] Next, the molding powder obtained by mixing is molded into a desired shape. As the molding method, a method commonly used for molding ceramics, such as uniaxial pressing, slip casting, extrusion, doctor blade, etc., can be adopted. Depending on the molding method, the molding powder may be mixed in advance with a binder, a plasticizer, a dispersant, etc. to form a molding composition.
[0048] In the case where the sintered body includes an internal electrode, that is, where the sintered body has a layered structure of ceramics and electrodes, the forming method may be such that the forming powder is mixed with a binder or the like to form a slurry or clay, which is then formed into a sheet to form a green sheet, an internal electrode pattern is formed on the green sheet, and then a predetermined number of green sheets are laminated and bonded in a predetermined order. In this case, the internal electrode pattern is shaped so that every other layer can be connected in the lamination direction. The internal electrode pattern may be formed by a conventional method, and a method of printing or applying a paste containing an electrode material is preferable in terms of cost. When forming an electrode pattern by printing or applying, a powder (co-material) having the same composition as the glass frit or the forming powder may be included in the paste in order to improve the adhesion strength to the ceramic after firing.
[0049] Finally, the molded body is fired to obtain a sintered body. When the molded body contains organic components such as binders, plasticizers, or dispersants, the organic components are removed prior to firing. In this case, the removal of the organic components and firing may be performed consecutively using the same firing apparatus. Examples of firing conditions include 850 to 1100°C in an air atmosphere for 1 to 5 hours.
[0050] In the second aspect, the prepared sintered body is placed in water that is higher than room temperature. Here, "room temperature" means a temperature at which no cooling or heating is performed, and generally refers to a temperature of about 5 to 35°C. Also, "placed in water" means that the entire surface of the sintered body is in contact with water. Examples of the manner of placing in water that is higher than room temperature include immersion in warm water and placement in a heated atmosphere containing moisture exceeding the amount of saturated water vapor. By placing the sintered body in water that is higher than room temperature, Li3NbO4 generated on the surface of the sintered body during firing is decomposed or removed. From the viewpoint of promoting the decomposition or removal of Li3NbO4, the temperature of the water in which the sintered body is placed (contacting the sintered body) is preferably 60°C or higher, more preferably 70°C or higher, and even more preferably 80°C or higher. Also, the time for immersion or placement is preferably 20 minutes or more, more preferably 30 minutes or more, and even more preferably 1 hour or more. The higher the water temperature, the shorter the time required for decomposition or removal of Li3NbO4. Therefore, from the viewpoint of improving productivity, it is preferable to use high-temperature water and shorten the placement time.
[0051] The sintered body with the above arrangement may be heat-treated at 300 to 900°C in air prior to the formation of the electrodes described below. As a result, even if Li compounds and Nb compounds remain on the surface of the sintered body after the decomposition of Li3NbO4, they react to generate LiNbO3, which has high chemical stability and electrical insulation. Therefore, the deterioration of the surface of the sintered body in a high-temperature and high-humidity environment is significantly suppressed, and the occurrence of failures is suppressed. In addition, the high electrical insulation of LiNbO3 reduces the risk of short circuits and insulation breakdown.
[0052] Next, electrodes are formed on the surface of the sintered body. Methods for forming the electrodes include a method of printing or applying an electrode paste and then baking it, and a method of depositing an electrode material. When forming the electrodes by baking, LiNbO3 may be generated on the surface of the sintered body by the mechanism described above when the sintered body is heated. The materials described in the first aspect can be used as the material for the electrodes.
[0053] Finally, a voltage is applied between the electrodes to perform a polarization process. This aligns the direction of spontaneous polarization in the ceramic, resulting in the development of piezoelectricity. The conditions for the polarization process are not particularly limited as long as they can align the direction of spontaneous polarization in the ceramic without causing damage such as cracks in the sintered compact. One example is application of an electric field of 4 to 6 kV / mm at a temperature of 100 to 150°C.
[0054] [Piezoelectric vibration device] The piezoelectric element according to the first aspect is suitably used in a piezoelectric vibration device. Therefore, as a third aspect of the present invention, a vibration device using the piezoelectric element will be described. The vibration device according to the third aspect of the present invention operates by applying an electric signal to the piezoelectric element to vibrate it, thereby vibrating the diaphragm. The material of the diaphragm used is not particularly limited as long as it vibrates due to the vibration of the piezoelectric element, and can be, for example, a resin such as polycarbonate or acrylic, a metal such as SUS or brass, or glass, etc. The size and shape of the diaphragm are also not particularly limited, and can be, for example, a rectangular plate, a polygonal plate, a circular plate, or an elliptical plate with a thickness of 10 to 500 μm. The means for bonding the piezoelectric element to the diaphragm is not particularly limited as long as it can efficiently transmit the vibration of the piezoelectric element to the diaphragm, and adhesives such as epoxy resins or double-sided tape can be used. EXAMPLES
[0055] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0056] Comparative Example 1 [Production of calcined powder] High-purity lithium carbonate (Li2CO3), sodium carbonate (Na2CO3), potassium carbonate (K2CO3) and niobium pentoxide (Nb2O5) were used as starting materials. These starting materials are mixed together to obtain a calcined powder with the formula Li 0.06 Na 0.52 K 0.42The mixture was weighed out so as to become NbO3, and wet-mixed in a ball mill. The mixed slurry was dried to obtain a mixed powder, which was then calcined in air at 900° C. for 3 hours to obtain a calcined powder.
[0057] [Production of Molded Products] The calcined powder was mixed with high-purity lithium carbonate (Li2CO3), strontium carbonate (SrCO3), manganese carbonate (MnCO3) and silicon dioxide (SiO2) to obtain Li 0.06 Na 0.52 K 0.42 A powder for molding was obtained by adding 1.3 mol of Li, 0.5 mol of Sr, 0.5 mol of Mn, and 1.3 mol of Si to 100 mol of NbO3. The obtained molding powder was mixed with a polyvinyl butyral binder to obtain a molding composition. The obtained molding composition was molded with a doctor blade to obtain a green sheet having a thickness of 80 μm. A conductive paste containing Ag and Pd in a mass ratio of Ag / Pd=7 / 3 was screen-printed on the green sheet in a desired pattern. After the conductive paste was dried, 30 green sheets were stacked and pressed at a pressure of about 50 MPa while heating to obtain a molded body.
[0058] [Manufacturing of sintered bodies] The obtained green body was cut into individual pieces, subjected to a binder removal treatment in the air, and then fired in the air at 1100° C. for 3 hours to obtain a sintered body.
[0059] [Manufacturing of piezoelectric elements] Ag paste was applied to the opposing side surfaces (surfaces parallel to the direction in which the green sheets were stacked) of the obtained sintered body so as to cover the ends of the internal electrodes exposed on each side surface, and then the body was passed through a belt furnace set at 800° C. and baked to form a pair of electrodes. The sintered body after the electrodes were formed was placed in a thermostatic chamber at 100° C., and an electric field of 3 kV / mm was applied between the electrodes for 15 minutes to perform a polarization process, thereby obtaining a piezoelectric element according to Comparative Example 1.
[0060] [Confirmation of the presence or absence of LiNbO3 on the surface of sintered body] The presence or absence of LiNbO3 on the surface of the sintered body of the obtained piezoelectric element was confirmed by the above-mentioned method. LN = 0.47, and it was determined that LiNbO3 was not contained. The result of X-ray diffraction measurement (diffraction line profile) of the surface of the sintered body of the piezoelectric element according to Comparative Example 1 is shown as (a) in Figure 1. A peak of Li3NbO4 was confirmed in the diffraction line profile.
[0061] [Manufacturing of piezoelectric vibration device and measurement of vibration plate attachment strength] A 500 μm thick SUS plate (made of SUS304) was bonded as a vibration plate using an epoxy-based adhesive to the upper surface of the piezoelectric element of Comparative Example 1, i.e., one of the surfaces perpendicular to the direction in which the raw sheets were stacked, to obtain a piezoelectric driving device of Comparative Example 1.
[0062] A tensile test was performed on the obtained piezoelectric actuator by applying a tensile load between the vibration plate and the piezoelectric element in the direction perpendicular to the adhesive surface of the vibration plate using a load-displacement measurement unit (FSA series, manufactured by Imada Co., Ltd.). The maximum stress until the vibration plate peeled off from the piezoelectric element was taken as the vibration plate adhesion strength. The obtained vibration plate adhesion strength was 18 N / cm 2 In addition, a piezoelectric vibration device manufactured in the same manner was placed in a thermo-hygrostat set at 40°C and a relative humidity of 90% for 24 hours, and then a tensile test was carried out in the same manner. The adhesion strength of the vibration plate was 0.7 N / cm 2 and dropped significantly.
[0063] [Confirmation of the stability of Li3NbO4 contained on the surface of sintered body] In order to confirm that the above-mentioned decrease in the adhesion strength of the diaphragm is due to the decomposition of Li3NbO4 contained in the surface of the sintered body, and that the Li3NbO4 can be decomposed or removed by placing the sintered body in water at a temperature higher than room temperature, the sintered body obtained by firing was immersed in warm water at 80°C for 30 minutes for measurement samples, and X-ray diffraction measurements were performed in the same manner as for confirming the presence or absence of LiNbO3. The obtained diffraction line profile is shown in Figure 1 as (b). In the diffraction line profile, it was confirmed that the peak of Li3NbO4 (see Figure 1 (a)) seen in the piezoelectric element before immersion in warm water had disappeared. From this result, it can be seen that Li3NbO4 contained in the surface of the sintered body has low chemical stability and is decomposed by the action of water in a high-temperature and high-humidity environment, which causes a decrease in the adhesion strength of the diaphragm. In addition, it can be said that by placing the sintered body in water at a temperature higher than room temperature, the Li3NbO4 contained in the surface of the sintered body is decomposed or removed, and the decrease in the adhesion strength of the diaphragm is suppressed.
[0064] [Evaluation of Ag migration from electrodes] After placing the piezoelectric vibration device in a high-temperature, constant-humidity chamber at 40°C and 90% relative humidity for 24 hours, an AC unipolar drive test was performed in the same high-temperature, constant-humidity chamber under the conditions of 3 kV / mm, 50 Hz, and 2 million cycles. For the piezoelectric ceramic part exposed on the surface of the piezoelectric vibration device after the test, the vicinity of the electrode that was the positive pole during the drive test was surface analyzed using SEM-EDS (FE-SEM (S-4300) manufactured by Hitachi High-Technologies Corporation equipped with a silicon drift type energy dispersive X-ray detector (Appolo) manufactured by Ametech Co., Ltd.), and the degree of Ag migration from the electrode was evaluated based on the mapping image showing the distribution of Ag. Since the area with high Ag concentration in the mapping image extended to a position more than 400 μm away from the electrode, it can be said that the piezoelectric drive device according to Comparative Example 1 actively undergoes Ag migration during drive when placed in a high-temperature, high-humidity environment.
[0065] Example 1 [Manufacturing of piezoelectric elements and confirmation of the presence or absence of LiNbO3] A sintered body manufactured in the same manner as in Comparative Example 1 was immersed in 80°C warm water for 30 minutes, and then heat-treated in air at 600°C for 30 minutes to obtain a sintered body. Electrodes were formed and a polarization treatment was performed on the sintered body in the same manner as in Comparative Example 1 to obtain a piezoelectric element according to Example 1. The presence or absence of LiNbO3 in the surface of the sintered body of the obtained piezoelectric element was confirmed in the same manner as in Comparative Example 1, and it was found that I LN = 2.1, and it was determined that LiNbO3 was contained. In addition, when the presence or absence of LiNbO3 in the part 5 μm or more deep from the surface was confirmed by the above-mentioned method, I LN = 0.73, and it was determined that LiNbO3 was not contained. The result of X-ray diffraction measurement (diffraction line profile) of the surface of the sintered body of the piezoelectric element according to Example 1 is shown as (c) in Fig. 1. In the diffraction line profile, it was confirmed that the peak of Li3NbO4 (see Fig. 1 (a)) seen in the piezoelectric element according to Comparative Example 1 had disappeared, and a peak of LiNbO3 had appeared.
[0066] [Manufacturing of piezoelectric vibration device and measurement of vibration plate attachment strength] A vibration plate was attached to the piezoelectric element according to Example 1 in the same manner as in Comparative Example 1 to obtain a piezoelectric driving device according to Example 1. When the vibration plate adhesion strength of the obtained piezoelectric driving device was measured in the same manner as in Comparative Example 1, it was 18 N / cm immediately after manufacture. 2 , and after placing in a temperature and humidity chamber, it was 17N / cm 2 Thus, high adhesive strength was maintained.
[0067] [Confirmation of the stability of LiNbO3 contained on the surface of the sintered body] In order to confirm the stability of LiNbO3 contained in the surface of the sintered body of the piezoelectric element according to Example 1, the sintered body before the electrode formation was immersed in warm water at 80°C for 30 minutes to prepare a measurement sample, and the presence or absence of LiNbO3 in the surface of the sintered body was confirmed in the same manner as in Comparative Example 1. LNIt became 2.49 and it was determined that LiNbO3 was contained. The X-ray diffraction measurement result (diffraction line profile) of the measurement sample is shown as (d) in FIG. 1. In the diffraction line profile, no difference in the peak intensity of LiNbO3 could be confirmed between the diffraction line profile on the surface of the sintered body of the piezoelectric element according to Example 1 (see (c) in the same figure). From this result, it can be said that LiNbO3 contained on the surface of the sintered body of the piezoelectric element according to Example 1 has high chemical stability, and this contributes to the fact that the adhesion strength of the diaphragm hardly decreases even after being placed in a high-temperature and high-humidity environment.
[0068] [Evaluation of Migration of Ag from Electrodes] An AC drive test was performed on the piezoelectric vibration device after being placed in a thermo-hygrostat in the same manner as in Comparative Example 1. Regarding the piezoelectric vibration device after the test, the degree of migration of Ag from the electrodes was evaluated in the same manner as in Comparative Example 1. Since a region with a high Ag concentration in the mapping image was not observed in the piezoelectric ceramics portion, it can be said that the piezoelectric drive device according to Example 1 suppresses the migration of Ag during driving even when placed in a high-temperature and high-humidity environment.
[0069] From the above, the composition formula Li x Na y K 1-x-y When a piezoelectric ceramic mainly composed of a perovskite-type compound represented by NbO3 (however, 0.02 < x ≦ 0.1, 0.02 < x + y ≦ 1) and containing at least one alkaline earth metal selected from calcium, strontium, and barium and silver is placed in a high-temperature and high-humidity environment, the cause of failure lies in Li3NbO4 contained on the surface of the sintered body. By placing the sintered body in water at a temperature higher than room temperature, Li3NbO4 is decomposed or removed, and the occurrence of failure can be suppressed. Further, by heat-treating the sintered body after being placed in water at a temperature higher than room temperature in the atmosphere at 300 to 900 ° C., even when Li compounds and Nb compounds remain on the surface of the sintered body after the decomposition of Li3NbO4, these react to form LiNbO3 with high chemical stability and electrical insulation, and it can be said that the occurrence of failure is significantly suppressed. [Industrial Applicability]
[0070] According to the present invention, it is possible to provide a piezoelectric element using an alkali niobate piezoelectric ceramic that is unlikely to break down even when placed in a high-temperature, high-humidity environment. As a result, the present invention is useful in that it can suppress the occurrence of failures even when the piezoelectric element and various devices equipped with the piezoelectric element are placed in a high-temperature, high-humidity environment that is not expected in normal usage conditions due to user negligence or unavoidable circumstances. In addition, a preferred embodiment of the present invention is useful in that it contains LiNbO3, which has excellent chemical stability and electrical insulation properties, on the surface of the sintered body, thereby significantly suppressing the occurrence of failures and reducing the possibility of short circuits and insulation breakdown.
Claims
1. Composition formula Li x Na y K 1-x-y NbO 3 (wherein 0.02<x≦0.1, 0.02<x+y≦1) as a main component, Contains at least one alkaline earth metal selected from calcium, strontium, and barium, and silver. It is made of piezoelectric ceramics. LiNbO 3 Contains LiNbO 3 Does not contain Sintered bodies, and At least one pair of electrodes formed on the surface of the sintered body A piezoelectric element comprising:
2. 2. The piezoelectric element according to claim 1, wherein the content of said alkaline earth metals is 0.2 to 5.0 moles in total per 100 moles of said main component.
3. 3. The piezoelectric element according to claim 1, wherein the content of said silver is 0.5 to 5.0 mol per 100 mol of said main component.
4. 4. The piezoelectric element according to claim 1, wherein the piezoelectric ceramic further contains 0.1 to 3.0 mol of Li and 0.1 to 3.0 mol of Si per 100 mol of the main component.
5. 5. The piezoelectric element according to claim 1, wherein the piezoelectric ceramic further contains 0 to 2.0 mol of Mn per 100 mol of the main component.
6. The piezoelectric element according to any one of claims 1 to 5, wherein the at least one pair of electrodes comprises silver.
7. Composition formula Li x Na y K 1-x-y NbO 3 (wherein 0.02<x≦0.1, 0.02<x+y≦1) is a perovskite-type compound as a main component, and a sintered body formed of a ceramic containing at least one alkaline earth metal selected from calcium, strontium, and barium, and silver; placing the sintered body in water at a temperature higher than room temperature to decompose or remove Li 3 NbO 4 on the surface of the sintered body; forming at least one pair of electrodes on the surface of the sintered body after the arrangement; and A voltage is applied between the at least one pair of electrodes to perform a polarization process. A method for manufacturing a piezoelectric element, comprising:
8. A sintered body formed of a ceramic containing a perovskite compound represented by the composition formula Li x Na y K 1-x-y NbO 3 (where 0.02<x≦0.1, 0.02<x+y≦1) as a main component, at least one alkaline earth metal selected from calcium, strontium, and barium, and silver, is prepared; placing the sintered body in water at a temperature higher than room temperature; forming at least one pair of electrodes on the surface of the sintered body after the arrangement; and A voltage is applied between the at least one pair of electrodes to perform a polarization process. Including, The method for producing a piezoelectric element further comprises heat treating the arranged sintered body at 300 to 900° C. in air prior to forming the electrodes.
9. A piezoelectric vibration device comprising the piezoelectric element according to any one of claims 1 to 6 and a vibration plate joined to the piezoelectric element.
Citation Information
Patent Citations
Piezoelectric element, method of manufacturing piezoelectric element, piezoelectric actuator, and inkjet recording head
JP2009010367A
Method for manufacturing piezoelectric / electrostrictive material film, and powder composition used for manufacture thereof
JP2013189325A
Piezoelectric device and method for manufacturing the same
JP2017163055A
Laminated piezoelectric ceramic and manufacturing method thereof, laminated piezoelectric element, and piezoelectric vibrating device
JP2020147466A
Lamination type piezoelectric ceramic and manufacturing method thereof, and lamination type piezoelectric device and piezoelectric vibratory machine
JP2020167407A